Black Star, Bright Dawn - O'Dell, Scott, 1898-1989. (Boston : Houghton Mifflin, 1988)
Bright Dawn must face the challenge of the Iditarod dog sled race alone when her father is injured.
670
Accelerated Reader AR
Keywords: Eskimos -- Juvenile fiction; Sled dog racing -- Fiction; Survival -- Fiction; Eskimos -- Fiction; Indians of North America -- Fiction